Enhancing Enforcement Strategies Against Illegal Fishing: A Socio-Legal Analysis of Water Police Operations in Jakarta Waters under Law No. 45 of 2009 - Muharom Muharom; Muh Nasir; Abu Nawas (BULETIN ADALAH, 2026)
Illegal fishing remains a persistent challenge in Indonesia, undermining economic sustainability, marine ecosystems, and maritime security. Despite the enactment of Law No. 45 of 2009 on Fisheries, enforcement effectiveness particularly at the operational level remains uneven. This study addresses this gap by examining the strategies employed by the Water and Air Police Directorate (Ditpolair) of Korpolairud Baharkam Polri in combating illegal fishing in the waters of DKI Jakarta. Using a normative-empirical (socio-legal) approach, this research integrates statutory analysis with field data obtained through interviews and observations. The study evaluates enforcement practices, including maritime patrols, vessel monitoring, licensing inspections, and inter-agency coordination. The findings reveal that while current strategies have contributed to suppressing illegal fishing activities, their effectiveness is constrained by structural and operational limitations, including inadequate patrol assets, jurisdictional complexity, and increasingly adaptive criminal networks. This study argues that enforcement remains predominantly reactive and insufficiently supported by integrated surveillance systems and institutional synergy. Strengthening technological capacity, enhancing inter-agency collaboration, and adopting intelligence-led enforcement are critical to improving outcomes. This research contributes to the discourse on fisheries law enforcement by offering a practical and policy-oriented framework to optimize anti-illegal fishing strategies in high-risk maritime zones. Keywords: Illegal Fishing, Law Enforcement Strategy, Water Police, Fisheries Law, Indonesia.